[

link to www.basic-mathematics.com]

Copy and paste it into this math solver webpage.

See what the computer tells you the answer is.

6÷2(1+2)=y

You could sub all of these for variables:

6÷2*(1+2)=y

You always do bracket first (that IS the rules).

Thus it becomes:

6÷2*(3)=y

6÷2*3=y

I think we can all agree on that.

OK.............

Now let's sub these with some variables:

6÷2*3=y

n will now mean 3:

6÷2*n=y

Which becomes:

6÷2n=y

Let's rearrange to put all variable on one side.

6=2ny

Now let's solve for ny

6÷2=ny

3=ny

Now let's swap n back with a 3.

3=3y

Now let's solve for y.

3=3y

3÷3=y

1=y

I still get my same answer (because I followed the proper math-rules).